New species of Trichogramma Westwood (Hymenoptera: Trichogrammatidae) associated with lepidopterous eggs in Brazil - Querino, R. B.; Zucchi, R. A. (Zootaxa, 2003)
Four new species of Trichogramma are described: Trichogramma bertii n. sp. from Glena sp., a geometrid of silvicultural importance; Trichogramma esalqueanum n. sp. from Mechanitis lysimnia eggs, a minor pest of tomato and Heliconius erato phyllis; Trichogramma iracildae n. sp. from eggs of Calpodes ethlius; and Trichogramma pratissolii n. sp. collected from Anagasta kuehniella trap eggs (factitious host).